A transgressive ethics of alterity in Jhumpa Lahiri's and Rodica Mihalis's narratives of uprooting - Stoican, Adriana Elena (Primerjalna književnost, 2017)
The paper investigates Jhumpa Lahiri's and Rodica Mihalis' accounts of uprooting in order to highlight their common transcending mechanisms that facilitate dialogues across cultural differences. By presenting interactions between South Asian, Romanian and American characters, the authors promote a conception of cultures as changing systems that can become enriched by transfers of meanings beyond borders. Both authors illustrate how characters who come from dissimilar cultural contexts can engage in meaningful interactions. The Indian-American encounters as well as the Romanian-American intersections are portrayed as opportunities for human understanding beyond the individuals' specific affiliations. By providing examples of cultural agreement between protagonists from highly different backgrounds, both authors present ethical models of cultural interactions that reduce the possibility of cultural clashes. If we accept the premise that literary figures can serve as ethical models, the possibility of cross-cultural communication presented by Lahiri and Mihalis seems especially relevant in the contemporary context of intersecting migration routes and cultural flows. Although produced by authors from different cultural traditions, the narratives discussed promote a transcultural ethics that reveals the importance of shared values as antidotes to cultural collision.
Keywords: Lahiri, Jhumpa, 1967--; literature and ethics; migrations; Mihalis, Rodica, 195?-; literatura in etika; cultural identity; cultural values; human migration; migracije; interculturality; kulturna identiteta; kulturne vrednote; medkulturnost